Revisiting Sevsar: Towards a Possible Gnomon in the Armenian Highlands - Frincu, Marc Eduard; Perez-Enriquez, Raul; Aghikyan, Levon (Journal of Skyscape Archaeology, 2021)
The Armenian highlands contain numerous remote sites featuring petroglyphs. Many of these rock carvings are pastoral depictions of animals, while others are abstract and complex, and one example of the latter, believed by archaeologists to date back to the Late Bronze Age (LBA), is found on an isolated site on Sevsar Mountain at an altitude of about 2700 m. The most accepted theory about the significance of these carvings dates back to the 1980s and suggests that they were representative of a lunisolar calendar. During our two recent expeditions to the site in 2017 and 2019, we noticed a cup mark in the largest circular petroglyph, deep enough to hold a vertical wooden pole, and from this we inferred a more extensive astronomical function for the carvings. In particular, the petroglyph’s intricate design of a radiating spiral and three concentric circles placed at non-equidistant radii from the centre made us consider its possible use as a sundial, with the inscribed circles representing the noon shadow lengths on solstices and equinoxes. We measured the radii of the circles north–south and the orientation of the main landscape features using a Suunto clinometer and compass. Our analysis shows that the dimensions of the petroglyph closely match actual shadow lengths in the LBA, and that the petroglyph can be reconstructed to high accuracy from theoretical ellipses. Additionally, the remote location of this site further suggests that the movement of the Sun was important to the builders, as the site may have also served as a ritualistic and initiation destination.